(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Unemployment is the largest issue in the economy. Additionally, it can certainly be defined individuals that have the ability and capability to the office though they cannot look for a task in a workforce. You will find 2 major reasons for unemployment i.e., the social issues as well as incorrect authorities’ policies. This particular paper examines the root cause of unemployment in India. Relationship between Economic Employment and Growth is additionally talked about in this specific paper. Together with its a present scenario of unemployment is offered. This particular paper additionally indicates some measure to get over of these burning up issues of unemployment.